Carcinoid tumors of the digestive system - Estrugo, Roberto; D'Auria, Agustín; Gardiol, Valdo; Bercianos, Carlos; Perdomo, Roberto (Cirugía del Uruguay, 1973)
The paper covers a case material of 10 carcinoid tumors of the digestive tract and discusses their clinical aspects and therapy. Two were rare, being located in the. cystic duct ( the only case in world literature available) and in the duodenum (having started as a perforation in the free peritoneum). National bibliography was increased by two cases of carcinoid tumor accompanied by carcinoid syndrome.